Estimation of Physical Impact Efficiency in Modifying Cast Alloys Used in Mechanical Engineering - Prikhodko, Olga; Gutak, Olga; Deev, Vladislav (Applied Mechanics and Materials, 2014)
The paper address the method of assessing the effectiveness of various physical modifying impacts on cast alloys used in mechanical engineering. The method is based on defining the quantity of solid phase calculated by means of the Delphi visual programming language. The study of mechanical properties and microstructure of the alloy AS7p confirmed the results of calculationsIn modern foundry in casting units with required properties the choice of an alloy casting technology and processing of items in a liquid state plays a significant role in machine building.